(untitled) (Zien Journal of Social Sciences and Humanities, 2021)
Consumer organizations such as Consumers Union, Medical Organization can design program or medical aid campaign to help consumers select options that will provide optimal health and financial outcomes to fitness and health care so that Consumers can have information about medical care as well as financial solutions to acquire fitness and health care. The objective of the research is to understand Psychographic aspect of Consumer Behavior for health services and accordingly effort to understand how proactive behavior can be inculcate amongst consumers. Data was collected from primary source which are Medical Practitioners, Medical Representatives and Patients. Research method is adaptive as it tries to influence present psychographic consumer behavior towards health and fitness and to measure responses likert scale is used. To do optimal health and financial outcomes to fitness the research method is both Qualitative as well as Quantitative. Structured and unstructured questionnaires are used for all primary sources and for measuring some responses tabulations are graphed for conclusive and descriptive findings. Consumers confidently choose products that provide the best value for the money. When it comes to choosing medicines and care, they often find themselves confused. This research has contributed in two ways, one to know consumer behavior for health services for medical service providers so that they can develop communication programs and secondly consumer awareness regarding medical care and financial aid.